MEMBANGUN JIWA KEWIRAUSAHAAN DI ERA DIGITAL DI DESA MARUYUNGSARI KECAMATAN PADAHERANG KABUPATEN PENGANDARAN: MEMBANGUN JIWA KEWIRAUSAHAAN DI ERA DIGITAL DI DESA MARUYUNGSARI KECAMATAN PADAHERANG KABUPATEN PENGANDARAN (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of the service is to provide an understanding of the importance of using Digital marketing to market products for Micro, Small and Medium Enterprises. Provide motivation for entrepreneurship after the pandemic. As a result of the pandemic, there has been a decline in sales, many of whose businesses have stagnated, even almost died. There are problems in the midst of these difficulties, it is necessary to have a defense strategy to keep running the business. Strategies for running a business during a pandemic, one of which is using Digitalization. Digitizing UMKM (Micro, Small and Medium Enterprises) is an effort to digitize the marketing of MSME products by MSME actors. Digital marketing makes it easier for businesses to market and sell their products online. Digitizing MSMEs is an effort so that MSME actors (Business, Micro, Small and Medium Enterprises) begin to move to the digital realm in their business activities. The target of this community service is business owners and MSMEs in Maruyungsari village, Padaherang sub-district, Pangandaran Regency. The service will be held on September 3, 2022. The method used is the lecture method from the service team and discussion about the service material. In the implementation of the activity, pre-test and post-test were carried out orally. This is done to find out the understanding of owners and employees about digital marketing. The results of the dedication are the owners of UMKM in Maruyungsasri Village better understand digital marketing and start learning to practice it to market their products, even though it is still at a simple level. Keywords : digital Marketing ,UMKM